Accuracy of vertical bitewing radiography in determination of root length of maxillary primary molars - Mahtab Hamzeh; Farida Abesi; Soraya Khafri; Ana Rakhshandejoo (Babol University of Medical Sciences, 2018)
Introduction: Considering the good geometry and possibility of simultaneous observation of the roots of the maxillary and mandibular molars in vertical bitewing radiography, the present study was conducted to evaluate the accuracy of vertical bitewing radiography in determination of root length of maxillary primary molars. Materials & Methods: One hundred first primary molars and forty second primary molars which were planned to be extracted for reasons other than this study, were used in this cross-sectional study. All radiographs were taken by a radiologist with vertical bitewing technique using XCP pediatric bitewing film holder. The root length was measured from the highest visible point of the occlusal surface to the most apical point of the root using caliper with accuracy of 0.1 mm. After removing the teeth, the length of each root was measured from the highest point at the occlusal surface to the tip of the root. Data were entered into SPSS 20 and analyzed using Pearson correlation and one sample t-test. Significance level was considered as 0.05. Results: According to the results of one sample t-test, although the root length was estimated slightly higher than the actual size in all cases, the difference was significant only for distobuccal root of the first primary molar (P˂0.05). The results of Pearson correlation test showed that in 95% of cases, the true root length values were consistent with those measured by radiography. Conclusion: Based on the results of this study, except for distobuccal root of first primary molar,  the vertical bitewing could precisely determine the root length of primary molars.